Abstract 13721: The Monitoring of rSO2 Value During CPR is Useful for High-Quality CPR - Ogawa, Yoshihito; Shiozaki, Tadahiko; Hirose, Tomoya; Ohnishi, Mitsuo; Tajima, Goro; Nishimura, Tetsuro; Kishi, Masashi; Ogura, Hiroshi; Shimazu, Takeshi (Circulation, 2015)
[Background] Recently, the patients with out-of-hospital cardiac arrest are increasing. It is very important to do chest compression continuously for the return of spontaneous circulation (ROSC). But we can not but stop chest compression during checking pulse every few minutes. We reported that Regional cerebral Oxygen Saturation (rSO2) value was not elevated by manual chest compression and mechanical chest compression increased a little rSO2 value on CPR without ROSC and rSO2 value became a good parameter of ROSC in single center study.[Purpose] The purpose of this study is to evaluate clinical utility of rSO2 value during CPR in multicenter study.[Method] Retrospectively, we considered the rSO2 value of the out-of -hospital cardiac arrest patients from December 2012 to December 2014 in multicenter. During CPR, rSO2 were recorded continuously from the forehead of the patients by TOS-OR (Japan). CPR for patients with OHCA was performed according to the JRC-guidelines 2010.[Result] 252 patients with OHCA were included in this study. The rSO2 value on arrival, during CPR and ROSC were 44.4±8.9%, 45.4±9.7%, 58.6±9.2%. In ROSC, with rSO2 cutoff value of 52.7%, the specificity and sensitivity were 80% and 79%, respectively. The negative predict value was 99.2%, respectively. It means little possible to ROSC, if the rSO2 value is less than 52.7%. So, it may be possible to reduce the frequency of checking pulse during CPR.[Conclusion] The monitoring of rSO2 value could reduce the frequency of checking pulse during CPR and do chest compression continuously.